143k views
1 vote
Suppose that the functions q and r are defined as follows.

q (x) = x^2+6
r(x) = square x+9

Suppose that the functions q and r are defined as follows. q (x) = x^2+6 r(x) = square-example-1

1 Answer

4 votes

Answer:


(r\circ q)(7)=8,\ (r\circ q)(7)=-8


(q\circ r)(7)=22

Explanation:

Composite Function

Given two functions q(x) and r(x), the composite function
r\circ q(x) is defined as


(r\circ q)(x)=r(q(x))

Similarily


(q\circ r)(x)=q(r(x))

The functions are


q(x)=x^2+6


r(x)=√(x+9)

Compute


(r\circ q)(x)=√(x^2+6+9)=√(x^2+15)

Evaluating for x=7


(r\circ q)(7)=√(7^2+15)=√(64)=\pm 8

We have two solutions


\boxed{(r\circ q)(7)=8,\ (r\circ q)(7)=-8}

Now compute


(q\circ r)(x)=(√(x+9))^2+6=x+9+6=x+15

For x=7


(q\circ r)(7)=7+15=22


\boxed{(q\circ r)(7)=22}

User Eddy Hernandez
by
4.1k points